Coronavirus infection (COVID-19) during pregnancy and its therapeutic management. A bibliographic review. - Cumbe-Martínez , Cristina (2022)
Introduction: COVID-19 produced a global health emergency. In addition to little knowledge about the effect of this infection on pregnancy, there are doubts about its impact on the product of pregnancy. Although it is known that pregnant women are particularly vulnerable, there is no particular management scheme for them; although there are reports of the use of several drugs, similar to the treatment in other adults without pregnancy. Objective: Learn about the infection by COVID-19 in pregnancy and its treatment Materials and Methods: a theoretical review was carried out, as sources of information the libraries were taken into account: MEDLNE, EMBASE, PubMed and Cochrane. A search based on mesh terms was performed. Publications on this topic were included, with a bibliographic, observational or analytical review design. Results: 43 publications were found, of which ten were suppressed and 33 were included. Therapeutic actions to address Covid-19 in pregnancy encompass three pillars: prevention actions, hospital admission, and individualized therapeutic management. Conclusion: In pregnant women with COVID-19, the management is not different from that used in the rest of the adults; includes individualized care, according to the patient's condition, aimed at guaranteeing the survival of the mother-fetus binomial. More research is needed to objectively argue these results in favor of the critical points of discussion that are described in the present review, since it is a disease of recent onset.